Dialogue Between Humanity, Nature, and Islam: A Philosophical Perspective of Mama Aleta's Ecofeminist Struggle - Zakaria Ansori; Wahyu Trisno Aji (Millati: Journal of Islamic Studies and Humanities, 2025)
This article examines Mama Aleta’s struggle within the theoretical framework of ecofeminism. Employing a qualitative literature review with an analytical-philosophical approach, the study draws on data from books, journals, articles, and credible online sources related to ecofeminism and Mama Aleta’s activism. The findings reveal that communities in Eastern Indonesia, particularly the Mollo people, hold a holistic and spiritual worldview in which nature is recognized as a sacred part of human existence. Nature is not perceived as a mere object of exploitation, but as a source of life, identity, and cultural continuity that must be safeguarded for future generations. Mama Aleta’s resistance to large-scale mining in Mollo territory symbolizes a profound ecofeminist consciousness: caring for the environment is inseparable from protecting human dignity and maintaining the integrity of God’s creation. Framed within Islamic ethical perspectives, this struggle aligns with the Qur’anic concept of humankind as khalīfah (trustees of the Earth), tasked with rejecting greed while upholding harmony between humans, nature, and the Divine. The study thus argues that Mama Aleta’s activism represents a powerful articulation that the defense of nature is inherently a defense of life, particularly women’s lives, since environmental destruction disproportionately impacts women’s roles, bodies, and social realities.